2006
DOI: 10.4315/0362-028x-69.2.345
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Inactivation of Staphylococcus aureus in Skim Milk by Combining High-Intensity Pulsed Electric Fields and Nisin

Abstract: High-intensity pulsed electric fields (HIPEF) can be used as a nonthermal preservation method that is believed to enhance the effect of nisin on microorganisms such as Staphylococcus aureus. The survival of S. aureus inoculated into skim milk and treated with nisin, with HIPEF, or with a combination of nisin-HIPEF was evaluated. Nisin dose, milk pH, and HIPEF treatment time were the controlled variables that were set up at 20 to 150 ppm, pH 5.0 to 6.8, and 240 to 2,400 micros, respectively. HIPEF strength and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(38 citation statements)
references
References 45 publications
1
37
0
Order By: Relevance
“…When the electrical conductivity of the carrot juice was measured at 25°C, an electrical conductivity of 9.72 mS/cm was obtained, which is a high value. Milk also has a high electrical conductivity of 6.98 mS/cm at a temperature of 25°C (Sobrino-López and Martín-Belloso 2006). Thus, among the liquid foods reported in literature related to HIPEF treatment, carrot juice and milk had the highest electrical conductivity.…”
Section: Characterization and Electrical Conductivity Studymentioning
confidence: 91%
“…When the electrical conductivity of the carrot juice was measured at 25°C, an electrical conductivity of 9.72 mS/cm was obtained, which is a high value. Milk also has a high electrical conductivity of 6.98 mS/cm at a temperature of 25°C (Sobrino-López and Martín-Belloso 2006). Thus, among the liquid foods reported in literature related to HIPEF treatment, carrot juice and milk had the highest electrical conductivity.…”
Section: Characterization and Electrical Conductivity Studymentioning
confidence: 91%
“…Sampedro et al [41] added that this thermal injury perturbed the physical stability and fluidity of the cell membrane. As a result, membranes may lose their elastic properties as temperature increases in accordance with the phospholipid phase transition from gel to liquid-crystalline [54].…”
Section: Influence Of the Process Variablesmentioning
confidence: 94%
“…The variation in the antimicrobial effect was attributed to local changes in the pH of the area surrounding the cell envelope that favoured the subsequent solubilisation of the bacteriocin. However, cell death reached its optimum level as described by the fitted second order model (Sobrino-López et al 2006a). Lowering PEF treatment time and increasing the nisin concentration enhanced the lethality for S. aureus in skim milk at pH 5.0; whereas the opposite was true at the natural pH (6.8) of milk (Fig.…”
Section: Pef and Added Nisinmentioning
confidence: 96%
“…Hodgins et al (2002) found that cell death in natural flora fell from 5.5-log units to 6.8-log units when orange juice containing 100 IU/mL added nisin was acidified from 4.0 to 3.5 under equal PEF conditions. Sobrino-López et al (2006a) studied the variation in the survival fraction of S. aureus in milk as a function of pH, nisin dose and PEF treatment time in greater detail (Fig. 2).…”
Section: Pef and Added Nisinmentioning
confidence: 99%